Damages of Underground Facilities in Coal Mines due to Gas Explosion Shock Waves: An Overview - Dezhi Ran; Jianwei Cheng; Rui Zhang; Yu Wang; Yuhang Wu (Shock and Vibration)
With coal mining depth increase, gas explosion accidents due to the high gas emission rates often occur which cause significant casualties and property damages. Among them, gas explosion shock waves not only can destroy the machines and equipment in mine roadways but also cause the failure of mine ventilation facilities resulting in secondary hazards. Thus, the mines’ serious disasters could happen. For many years, researchers have already done a great lot of works to study damages caused by the impact of shock waves of the gas explosions in underground mines. Research results provide a baseline for judgments of hazard effects by explosions. In this paper, the formation mechanism of the gas explosion shock wave is introduced firstly. Then, the damages for underground facilities, such as mechanical equipment, roadway, and life-saving devices are summarized and reviewed. Finally, a brief discussion about the methods is given, and some preliminary suggestions are also listed for improvements in the future.